Pengaruh Media Stiker Ibadah Shalat Terhadap Kemampuan Gerakan Shalat Anak Usia Dini - Andepi Daryana; Enur Hayati (Idarotuna: Jurnal Manajemen Pendidikan Islam, 2024)
The background of the research problem is that group B RA RA RIYADLUL HUDA students have not been able to perform prayer movements in the correct order, even though based on the decision of the Minister of Religion of the Republic of Indonesia Number 792 of 2018 children aged 5-6 years must be able to perform prayer movements in the correct order. This study aims to describe the application of prayer prayer sticker media to early childhood in group B at RA Riyadlul Huda in Malangbong, District Garut, what is the description of the development of the ability to pray for early childhood in group B at RA Riyadlul Huda, Malangbong, District Garut and how the influence of the prayer prayer sticker media on the ability to pray in group B at RA Riyadlul Huda Malangbong District, Garut. This type of research uses a quantitative approach. The subjects studied were group B RA Riyadlul Huda students, Malangbong, District Garut which amounted to 8 students. The data collection method was carried out through observation and documentation of a questionnaire with a Likert scale. Data analysis techniques use descriptive statistics. The results showed that there was an increase in students' ability to know the prayer movements and know the prayer readings. This was evidenced by the increase in the percentage of students' ability to know the prayer movements and know the prayer readings as indicated by the significance value of the simple linear regression test between variable X (prayer prayer sticker media). and the variable Y (the ability to pray) is 0.015 <0.05. This shows that there is a significant effect of variable X (media prayer stickers) on variable Y (ability to pray). The strength of the influence of variable X on variable Y is shown from the results of the coefficient of determination (R Square) which is equal to 96%.